Analysis of the Impact of Fiscal Policy on Regional Economic Growth: A Case Study of Implementation in Higher Education - Wira Yudha Alam; Aulia Pinkan Putri Shelari; Natasya Devaverdiani; Aulia Pasha Nagita Za’ara; Safina Fara Dhita (Dinasti International Journal of Management Science, 2026)
Fiscal policy is a strategic government instrument in promoting regional economic growth, particularly through budget allocation in the higher education sector. This study aims to analyze the impact of fiscal policy on regional economic growth, taking a case study of policy implementation in higher education institutions during the period 2015-2024. The study employs a mixed-methods approach, combining quantitative panel data analysis from 340 Universities in Indonesia and in-depth interviews with 30 informants consisting of lecturers, university structural officials, and regional policymakers. Secondary data were obtained from the Central Bureau of Statistics (BPS), the Ministry of Finance, and the Directorate General of Higher Education (Dikti). The results indicate that fiscal policies in the form of BOPTN Funds and Special Allocation Funds (DAK) for Education have a positive and significant effect on regional economic growth with a coefficient of 0.47 at a 95% confidence level. The findings also reveal that higher education institutions serve as a multiplier effect in driving the local economy through job creation, increased community consumption, and knowledge transfer. However, there are gaps in fiscal policy implementation between higher education institutions in Java and outside Java, which impact regional economic growth disparities. This study recommends the need for reformulation of fiscal policies that are more equitable and performance-based for higher education institutions to promote sustainable and equitable regional economic growth.